Research progress on PIEZO1 protein structure and activation mechanism by small-molecule agonists - Danjiang Li; Yuanyuan Song; Yuan Zeng; Hua Hu; Wei Tian (Results in Chemistry)
Piezo1, a non-selective cation channel, can transduce diverse mechanical stimuli into electrochemical signals and perform essential physiological functions in the human body. Anomalous Piezo1 activities due to loss-of-function mutations are linked to diverse pathological states ranging from anemia, malaria immunity, lymphatic abnormalities, and varicose veins. Thus, targeting and modulating Piezo1 have demonstrated the potential to yield significant therapeutic benefits, thereby affirming Piezo1 as a promising drug target for various diseases. Recent studies have unveiled crystal structures of Piezo1 and identified small-molecule agonists that shed light on the channel’s structure and activation mechanism. This review consolidates our understanding of Piezo1, focusing on its structural features, mechanosensitive activation and potential agonists to guide future investigations in this field.